Research on Innovative Marketing Strategies of Tourism Destination Brands under the Background of Cultural Tourism Integration - Zhu Haiqi (SHS Web of Conferences)
As the fusion of culture and tourism continues to accelerate, the branding strategies for tourist destinations are encountering both unprecedented challenges and fresh opportunities. This synergy not only amplifies the reciprocal benefits between cultural heritage and travel experiences but also opens up innovative avenues and platforms for crafting and promoting destination brands. This article delves into the ways tourism destination branding can be reimagined within this evolving landscape. By examining the essence and current trajectory of cultural tourism integration, alongside foundational theories of destination branding, it outlines creative approaches and methodologies for enhancing brand marketing strategies. The discussion concludes with a forward-looking perspective on the future trends shaping the marketing of tourism destinations.